Creativity and negotiation research: the integrative potential. Issue 4 (7th October 2014) - A Posthuma, Richard; Ruth Wilson, Elizabeth; L. Thompson, Leigh
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article is to outline ways in which the large body of empirical work on creativity can meaningfully inform negotiation. In doing so, two general streams of creativity research and their implications for negotiation theory and empirical analysis are considered. Negotiation pundits advise that negotiators should engage in creative problem-solving to craft integrative agreements, and it is widely believed by both negotiation theorists and practitioners that "out-of-the-box" thinking and creative idea generation are necessary for win–win negotiation. Although practitioners have strongly encouraged parties to engage in creative problem-solving, there are remarkably few empirical investigations of creative thinking, brainstorming and other idea-generation methods in negotiation. Design/methodology/approach – First, creativity as a trait is considered and the relationship between individual differences in creativity and negotiation performance is examined. Then, creative thinking as a causal factor is examined and how it may influence the negotiation process and outcomes is suggested. Finally, three considerations for further integrating creativity and negotiation research are suggested: communication media, idea-generation strategies and morality and social motivation. Findings – A literature review revealed four studies that have empirically tested the influence of trait creativity on negotiation performance. Even less research has manipulated creative thinking or training to analyze creativity as a causal factor of negotiation outcomes. Originality/value – This research will benefit both creativity and negotiation scholars by suggesting the limited amount of work at their intersection yet the opportunities that exist for further research.